New insights on the correspondence between subjective affective experience and physiological responses from representational similarity analysis. (11th May 2022) - Ventura‐Bort, Carlos; Wendt, Julia; Weymar, Mathias
Abstract: Classical views suggest that experienced affect is related to a specific bodily response, whereas recent perspectives challenge this view postulating that similar affective experiences rather evoke different physiological responses. To further advance this debate in the field, we used representational similarity analysis to investigate the correspondence between subjective affect (arousal and valence ratings) and physiological reactions (skin conductance response [SCR], startle blink response, heart rate, and corrugator activity) across various emotion induction contexts (picture viewing task, sound listening task, and imagery task). Significant similarities were exclusively observed between SCR and arousal in the picture viewing task. However, none of the other physiological measures showed a significant relation with valence and arousal ratings in any of the tasks. These findings are discussed within the framework of the Populations hypothesis, suggesting that physiological responses do not depend on the experienced affect but are directly associated with the context in which they are evoked. Abstract : We used representational similarity analysis to provide new insights into the relationship between subjective affect and physiological reactivity across three affect‐inducing tasks. Similarities between representational patterns of subjective affect and physiological reactivity only emerged for one physiological variable (SCR and arousal) in a specific context (i.e., passive picture viewing task). Our findings inform the ongoing debate on the relationship between physiological changes and the valence and arousal properties of affect.